Determinação de propriedades estruturais, elétricas e magnéticas da solução sólida de (1-x) BiFeO3-(x)PbTiO3 na região contorno de fases morfotrópico - Protzek, Otávio Augusto (2010)
The (1-x)BiFeO3(x)PbTIO3 system is classified as a multiferroic system, whose present magnetic and electric ordering. Furthermore, it possesses a morphotropic phase boundary that makes it a very attractive system for practical applications, since compositions at the morphotropic phase boundary can present enhanced physical properties. In this work, ceramic samples of the (1-x)BiFeO3(x)PbTiO3 system were synthesized by high-energy ball milling and conventional sintering, focusing their electrical, magnetic and structural characterization. The structural characterizations revealed that the morphotropic phase boundary was extended, from x = 0.29 to 0.40, as a function of the samples preparation protocol. In the morphotropic phase boundary region we identified the coexistence of perovskite phases with R3c and P4mm space groups. The whole set of dielectric, differential thermal analyses, ferroelectric and magnetic characterization data were dose to those reported in the literature, revealing the multiferroic nature of the ali studied samples. These samples presented high ferroeíectric and antiferromagnetic phase transition temperatures, and typical ferroelectric and magnetic hysteresis curves, which revealed their ferroelectric and weak-ferromagnetic character. A new phase diagram for the (1-x)BiFeO3(x)PbTiO3 system, which contam ferroelectric, magnetic and structural information about sampies in the morphotropic phase boundary, was constructed and proposed by using the whole set of the obtained results.